Assessing the economic and mitigation benefits of climate-smart agriculture and its implications for political economy: A case study in Southern Africa. (20th February 2021) - Branca, Giacomo; Arslan, Aslihan; Paolantonio, Adriana; Grewer, Uwe; Cattaneo, Andrea; Cavatassi, Romina; Lipper, Leslie; Hillier, Jonathan; Vetter, Sylvia
Abstract: Climate change poses a serious risk to the economic growth of sub-Saharan Africa. Sustainable enhancement of resilience and mitigation capacity of small farm households is a major political economy goal. This paper has the objective to assess the on-farm economic and mitigation benefits of climate-smart agriculture production and their cost-effectiveness to be used as a prioritization criterion for policy incentives. An interdisciplinary model which integrates elements of economics and ecological science at farm-scale is developed and applied using a unique dataset for Malawi and Zambia built through household surveys. Results show that switching from conventional to climate-smart farming enhances economic returns more significantly in semi-dry areas than in sub-humid ones. However, high up-front costs hinder technology adoption. Negative abatement costs for most smart farming options indicate synergies between livelihood enhancement and mitigation. Land management based on minimum tillage, crop residues incorporation, use of cover crops, and inclusion of legumes has relatively higher economic returns. Agroforestry provides lower economic returns but the highest emission abatement potential. Payments for mitigation benefits could be a management strategy to incentivize cleaner agriculture production if tailored appropriately. These results strengthen the case for public support to climate-smart agriculture scaling-up within policy and planning strategies. Graphical abstract: Image 1 Highlights: Climate-smart practices show synergies between livelihood improvement and mitigation. Climate-smart farming achieves more benefits in semi-dry areas than in sub-humid ones. Abatement cost curves visualize modelled evidence base to scale-up smart agriculture. Policies for smart techniques should prioritize cost-effective emission abatement. Climate finance to reward mitigation benefits must align with proven smart practices.